2021
DOI: 10.1109/jeds.2021.3108523
|View full text |Cite
|
Sign up to set email alerts
|

Analog Resistive Switching in BEOL, Ferroelectric Synaptic Weights

Abstract: A Ferroelectric, two-terminals, analog memristive device is fabricated with a Back-End-Of-Line, CMOS compatible process. A bilayer composed of a ferroelectric material, HfZrO4 (HZO) and a semiconducting oxide, WOx layer is comprised between two TiN electrodes. The devices demonstrate reversible and remanent resistive switching, with a record endurance (>10 10 switching cycles) and ON/OFF ratio up to 10. The analog resistive switching is obtained, with a cycle-to-cycle reproducibility of 90%. The synaptic behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…when carriers are not accumulated, but depleted in the later. This was already observed for WO x (3 nm)/HZO (5 nm) devices fabricated in similar conditions [18], where we showed that the resistive switching occurred within the HZO layer, the WO x layer being considered as a metal. In this work, the electric field is assumed to drop mainly across the ferroelectric layer (i.e., the thickness t is assumed to be the thickness of HZO, 2.7 nm).…”
Section: Effect Of Fatigue and Temperaturesupporting
confidence: 84%
See 3 more Smart Citations
“…when carriers are not accumulated, but depleted in the later. This was already observed for WO x (3 nm)/HZO (5 nm) devices fabricated in similar conditions [18], where we showed that the resistive switching occurred within the HZO layer, the WO x layer being considered as a metal. In this work, the electric field is assumed to drop mainly across the ferroelectric layer (i.e., the thickness t is assumed to be the thickness of HZO, 2.7 nm).…”
Section: Effect Of Fatigue and Temperaturesupporting
confidence: 84%
“…The as-grown HZO layer was amorphous [21]. Although 400 • C was sufficient to crystallize 5 nm thick films [18], in this work films flash-annealed at 450 • C did not show any sign of crystallization. The increased temperature required as the thickness decreases was observed by Tahara et al [17] on TiN/HZO/TiN stacks.…”
Section: Ultra-thin Hfzro 4 Based Devicesmentioning
confidence: 53%
See 2 more Smart Citations
“…The role of the WO x interlayer, as discussed in ref. [33], is to induce an asymmetry in the energy profile of the memristor, leading to a resistive switching effect driven by the ferroelectric domain switching. TiN was chosen as a capping layer to promote the crystallization of HZO in the ferroelectric phase by a mechanical constraint during the annealing.…”
Section: Ferroelectricity In Ultrathin Back-end Compatible Bilayermentioning
confidence: 99%